2020
DOI: 10.1007/s12237-019-00687-y
|View full text |Cite
|
Sign up to set email alerts
|

Dragonfly (Odonata) Diversity Patterns in Mixohaline Coastal Wetlands

Abstract: Check the metadata sheet to make sure that the header information, especially author names and the corresponding affiliations are correctly shown.• Check the questions that may have arisen during copy editing and insert your answers/corrections. • Check that the text is complete and that all figures, tables and their legends are included. Also check the accuracy of special characters, equations, and electronic supplementary material if applicable. If necessary refer to the Edited manuscript. • The publication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…Diplacodes trivialis, Neurothemis intermedia excelsa, N. terminata, Pantala flavescens, and Rhyothemis phyllis ixias. The majority of these taxa represent widespread generalist species, a pattern consistent with findings from coastal wetlands in North America (Wright 1943;McCreadie et al 2005;Catling et al 2006, Catling 2009) and Europe (Uboni et al 2020). In particular, diverse assemblages of odonates exploit brackish pools and salt marshes from Quebec and New Brunswick in Canada to the deltas of the Mississippi and Mobile rivers/Tensaw on the Gulf of Mexico (Wright 1943;McCreadie et al 2005;Catling et al 2006, Catling 2009.…”
Section: Dragonflies In Coastal Marshes and On Small Waterless Islandssupporting
confidence: 75%
See 1 more Smart Citation
“…Diplacodes trivialis, Neurothemis intermedia excelsa, N. terminata, Pantala flavescens, and Rhyothemis phyllis ixias. The majority of these taxa represent widespread generalist species, a pattern consistent with findings from coastal wetlands in North America (Wright 1943;McCreadie et al 2005;Catling et al 2006, Catling 2009) and Europe (Uboni et al 2020). In particular, diverse assemblages of odonates exploit brackish pools and salt marshes from Quebec and New Brunswick in Canada to the deltas of the Mississippi and Mobile rivers/Tensaw on the Gulf of Mexico (Wright 1943;McCreadie et al 2005;Catling et al 2006, Catling 2009.…”
Section: Dragonflies In Coastal Marshes and On Small Waterless Islandssupporting
confidence: 75%
“…In particular, diverse assemblages of odonates exploit brackish pools and salt marshes from Quebec and New Brunswick in Canada to the deltas of the Mississippi and Mobile rivers/Tensaw on the Gulf of Mexico (Wright 1943;McCreadie et al 2005;Catling et al 2006, Catling 2009. It was shown that at least 15 widespread Odonata species inhabit brackish wetlands in Europe (Uboni et al 2020). Saline inland lakes in North America can also support rather species-poor Odonata assemblages, comprising a few common, generalist species (Schwarz 1891;Osburn 1906;Cannings & Cannings 1987).…”
Section: Dragonflies In Coastal Marshes and On Small Waterless Islandsmentioning
confidence: 99%